2008
DOI: 10.1128/mcb.01659-07
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Dynamics of Global Chromatin Remodeling in Yeast: Dual Role for SWI/SNF in the Heat Shock Stress Response

Abstract: Although chromatin structure is known to affect transcriptional activity, it is not clear how broadly patterns of changes in histone modifications and nucleosome occupancy affect the dynamic regulation of transcription in response to perturbations. The identity and role of chromatin remodelers that mediate some of these changes are also unclear. Here, we performed temporal genome-wide analyses of gene expression, nucleosome occupancy, and histone H4 acetylation during the response of yeast (Saccharomyces cerev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
110
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 61 publications
10
110
0
Order By: Relevance
“…Affected genes do not fall into particular functional categories, although these data led to the discovery that Swi/Snf function is important for transcription during M phase (Krebs et al 2000). More recently, analysis of the heat-shock response showed that Swi/Snf directly regulates both ribosomal protein genes and genes under the control of heat-shock factor (Shivaswamy and Iyer 2008). These microarray studies likely underestimate the extent to which Swi/Snf controls transcription, as few conditions were tested.…”
Section: Regulation Of Transcription By Swi/snfmentioning
confidence: 99%
“…Affected genes do not fall into particular functional categories, although these data led to the discovery that Swi/Snf function is important for transcription during M phase (Krebs et al 2000). More recently, analysis of the heat-shock response showed that Swi/Snf directly regulates both ribosomal protein genes and genes under the control of heat-shock factor (Shivaswamy and Iyer 2008). These microarray studies likely underestimate the extent to which Swi/Snf controls transcription, as few conditions were tested.…”
Section: Regulation Of Transcription By Swi/snfmentioning
confidence: 99%
“…The two remodelers have very different binding distributions through the genome, with INO80 mapping to replication origins, tRNA genes, and a subset of RNA PolII promoters (Shimada et al 2008). Snf2 is present at high levels in ribosomal protein genes (Shivaswamy and Iyer 2008). Recent work has argued that INO80 preferentially exchanges Htz1-containing nucleosomes for canonical H2A/H2B dimers (PapamichosChronakis et al 2011), while SWI/SNF does not.…”
Section: The Mechanism Of Chromatin Movementmentioning
confidence: 99%
“…We therefore hypothesized that Set2 degradation might alter the levels of H3K36me2/me3 to facilitate transcription elongation during periods of transcriptional stress, when, for example, chromatin compaction by Rpd3(S) would inhibit rapid gene activation of stress response genes (47,48). To examine this possibility, by way of using mutant forms of Set2 that have different behaviors in degradation and H3K36me, we expressed the different truncated forms of Set2 (see Fig.…”
Section: Overexpression Of More Stable Form Of Set2(1-261) Is Lethal mentioning
confidence: 99%